Canon littéraire et enseignement de la littérature française au Canada anglais: L'exemple des femmes auteurs - Sauve, Rachel (Canadian Journal of Higher Education, 2001)
This article deals with the teaching of French classical literature in Canadian universities, and promotes new criteria in the selection of works to be taught: relevance of the work to its own times, its relevance for our times, and intertextual relevance. Preliminary remarks on theories of canon formation are followed by comments on the situation in Anglophone Canadian universities, supported by data on 19th Century French Literature courses. The example of women's writings, which is highly representative of the canon formation process, is developed and includes a survey of the current trends in the accessibility of women's writings on the Web, which confirms the continuing precedence of traditional criteria in the digitalization of literary texts. Nevertheless, the new technologies allow for a rethinking of the course format itself, which could be renewed by avoiding traditional period and author patterns, and by favoring the intertextual networking of literary texts, thus bringing about substantial changes in Canadian literature programs.